Mekanisasi Usahatani Padi Di Kecamatan Sananwetan Kota Blitar - Cristina Ratnawati (Manajemen Agribisnis: Jurnal Agribisnis, 2020)
This research purposes for determining the use of agricultural mechanization and its impact on rice farming in Sidomulyo Gapoktan, of Sananwetan District of Blitar City, which is expected to improve the living standards and welfare of its group members. The total samples which taken were 50 rice farmers of Sidomulyo Gapoktan in Sananwetan District of Blitar City. The sampling taken using purposive random sampling technique, which is deliberately chosed based on criteria which determined by the researcher. The Data analysis was carried out descriptively, using the Mann-Whitney Test and the Multiple Linear Regression Cobb Douglas model. Based on the results of the study, it was found that the mechanization of rice farming in Sidomulyo Gapoktan, Sananwetan District, Blitar City has not still optimal. This is caused by the farmers' perceptions of the results of unsatisfactory performance of agricultural machinery, a sense of humanity towards' farm labors, narrow area of farming and insufficient availability of agricultural machinery. The result of reseach which was used Mann-Whitney Test analysis, found that pesticide using and labor requirements were smaller and differed significantly in the use of full mechanization rather than partial mechanization. Harvest variable costs were lower in the use of full mechanization and were significantly different than using partial mechanisms. The Productivity of rice in full mechanization is 782,15 kg / 1000m2 while in partial mechanization was 682.87 kg / 1000m2. For farmers' income in full mechanization is Rp. 1,153,407, - per 1000 m2, in partial mechanization of Rp. 1,590,574, - per 1000m2. Multiple Linear Regression Analysis of the Cobb Douglas model shows that the land area (m2), seed costs and the use of mechanization have a significant influence on the income of rice farming in Sananwetan District, Blitar City.